Correlation between skin and clinical features in systemic sclerosis - Ljubinka Božić Majstorović; Snježana Popović Pejičić; Irma Ovčina; Verica Ivanović Prodanović; Jelena Mrdja (Биомедицинска истраживања, 2024)
Introduction: Systemic sclerosis (SS) is a complex autoimmune disease characterized by chronic progressive organic sclerosis. The aim of this paper is to show the correlation of ultrasound (US) parameters with Rodnan skin score (mRSS), as well as the clinical involvement of other organ systems. Methods: Our study included 24 patients diagnosed with SS and 24 healthy controls. We included demographic, clinical and laboratory parameters, individually and included in the European Scleroderma Trial and Research Disease Activity Index (EUSTAR-DAI) score. To measure skin involvement, we used the modified mRSS and skin ultrasound. Results: The skin thickness of patients and healthy controls measured by ultrasound showed statistically significant differences (p<0.001). Correlations between mRSS and anti-Scl-70 antibody (p=0.02) and between mRSS and diffusion capacity for carbon monoxide (DLCO) (p=0.03) were shown. Conclusion: In recent years, the importance of using skin ultrasound in patients with systemic sclerosis has been increasing, due to the fact that this technique can detect skin involvement in the early stages of the disease. The advantages of the method are availability and non-invasiveness, unlike skin biopsy. By standardizing ultrasound skin measurement, it would be possible to implement the method in daily clinical practice.
Keywords: ultrasound; scleroderma; skin